Effect of Gibberellic Acid and Superphosphate Fertilizer on Medical Compounds and Growth Characters of Fenugreek Plant (Trigonella foenumgraecum L.) Local Variaty (World Journal of Experimental Biosciences, 2017)
The study was carried out using pots (capacity, 4kg soil/pot) in the glasshouse and different concentrations of gibberellic acid (0, 25, 50 and 100) ppm and different levels of superphosphate (0.25, 0.50 and 100) gm/kg:soil/Pot, these equal to (83.33, 166.66 and 333.32) kg/hectar. In some medical compound which effect on Diabetes like coumrin, trigonellin and fenugreeken and some growth characters of fenugreek plant (local variety) like absolute growth rate, biomass duration, protein percentage, chlorophyll percentage and protein percentage in seeds were used. This factorial experiment (4× 3) was conducted by using complete randomizing design (C.R.D) with three replications, means were compared using the least significant difference at 0.05 probability level. The results could be summarized that the treatments by gebberllic acid (GA3) alone showed significant increase in absolute growth, biomass, chlorophyll content, protein percentage and medical compounds. While treatments with superphosphate fertilizer alone showed significant increase only in protein percentage and medical compounds. The interaction between GA3 and phosphate fertilizer showed the best results in all growth characters for all plants in this experiment, especially the treatment with 50 ppm of GA3 with 0.50 gm/pot and 1.0 gm/pot of superphosphate fertilizer gave the highest values of studied compared with control treatment.